A Critical Overview of Social Marketing in Asia. (December 2021) - Pang, Bo; Deshpande, Sameer A.; Nguyen, Tuyet-Mai; Kim, Jeawon; Almosa, Yara A.; Arif, Amna; Arli, Denni; Bakpayev, Marat; Erdogan, Bayram Zafer; Fujihira, Haruka; Gallage, H. P. Samanthika; Kadir, Mohammad A.; et al.
Background: Social marketing has been used in Asia to combat various social issues (Deshpande & Lee (2013). However, our understanding of social marketing awareness, adaptation, and achievement in Asian countries is limited. The focus of the Article: An historical overview of social marketing developments in Asia. Importance to the Social Marketing Field: This paper is one of the first attempts to integrate social marketing theory and practice in Asia to understand its strengths and weaknesses and to provide a recommendation to enhance the adoption and effectiveness of social marketing program design, implementation, and evaluation to generate social and behavioral change. Design/methodology/approach: The authors representing 18 Asian countries searched for social marketing growth and trends in prominence, conceptual developments, social issues and solutions, and effectiveness in English and local language literature. This paper describes themes by highlighting examples of initiatives. Findings: Our analysis reveals a broad spectrum of social marketing practices in Asia, focusing traditionally on managing overpopulation and preventing communicable diseases and, more recently, non-communicable diseases and climate action. The practice also revealed close integration with policies, overreliance on the government sector, lack of robust research studies, theorizing, documentation, training, and community involvement, and challenges presented by cultural factors and the confusion of understanding the term. Recommendations for research or practice: The study recommends establishing the Asian Social Marketing Association and Asian Social Marketing Institute, adopt a Total Market Approach, improve documentation, clarify the boundaries of social marketing, enhance the effectiveness of strategies by embracing research, involving the beneficiary communities, and by learning from others.